OUTCOME OF ELECTRIC SHOCK INJURIES: AN EXPERIENCE AT THE LADY READING HOSPITAL PESHAWAR - Haider, Ali; Zubair, Muhammad; Abideen, Zainul; Saima, .; Ihsanullah, .; Muner, Akhtar; Khan, Mohammad Nawaz; Musarat, .; Khattak, Azmatullah (Journal of Postgraduate Medical Institute, 2017)
Objectives: To determine the clinical presentation and outcome of accidental electric shock injuries in patients brought to the Department of Accident and Emergency, Lady Reading Hospital, Peshawar. Methodology: This descriptive study was conducted in the Department of Accident & Emergency, Lady Reading Hospital, Peshawar from 1st January 2011 to 31st December 2011.Patients with clear history of electric shock according to the patients or attendants were included in the study through consecutive sampling technique. Data was acquired through clinical history, physical examination and relevant investigations. Patients who were received dead and the attendants were not sure about the causes of death were excluded from the study. Data were analysed and presented in the form of tables. Results: A total of 219 patients were studied in which male and female were 161 (73.52%) and 58(26.5%) respectively. Age wise distribution showed that 106(48.4%) were in age range of 20-40 years. The majority of cases were brought in the months of July 38(17.4%), August 44(20.1%) and September 43(19.6%). Patients having only minor injuries were 64(29.2%) while dead were 34(15.5%). Patient having neurosurgical injuries were 23(10.5%) while orthopaedic injuries, poly trauma, burn injuries and cardiac arrhythmias were 21(9.6%), 19(8.7%), 11(5.0%) and 7(3.2%) respectively. Majority of patients 153(70%) were buried in ground due to the local myth before bringing to the hospital. Conclusion: Electric shock carries high morbidity and mortality. The majority of electric shock injuries occured in the summer rainy season.